RESEARCH ON GESTURE AND MOTION SYNCHRONIZATION TOOLS IN VR-WEB SPACE - ЛАТИШЕВ, Я.-В. Г.; МОСИСА, А. А. (Technologies and Engineering, 2024)
Purpose. The purpose of this research is a comprehensive analysis and optimization of gesture and motion synchronization tools in virtual reality using web technologies. The study focuses on identifying the most effective methods for integrating VR solutions into web space to enhance the naturalness and intuitiveness of user interaction with virtual environments. Special attention is given to exploring the capabilities of modern web platforms such as React XR and React 360 for developing interactive web VR applications that provide precise and smooth gesture and motion control for users. Methodology. The research is based on a comparative analysis of the effectiveness of existing web libraries for creating VR experiences, such as React XR and React 360. Experimental methods are employed to test different approaches to synchronization of gestures and motions, including motion sensors, cameras, and machine learning algorithms. Technical aspects of VR application implementation are examined, including the use of Kalman filter for motion correction and reactive programming for dynamic virtual environment updates. Empirical data is collected through a series of experiments with interactive web VR applications to evaluate the effectiveness of different synchronization methods. Findings. The analysis shows that the use of React XR and React 360 libraries significantly improves the quality and speed of developing web VR applications. React XR, due to its free availability, open-source nature, and active developer community, has proven more effective for rapid integration of VR solutions into web space. The use of the Kalman filter ensures accurate correction of user movements, enabling the creation of more realistic and immersive experiences. Additionally, synchronization methods based on sensors and computer vision algorithms allow precise tracking and smooth transmission of user gestures and movements into the virtual environment. Originality. The research provides a systematic analysis of the effectiveness of using React XR and React 360 libraries for gesture and movement synchronization by defining efficiency criteria such as gesture processing speed, animation smoothness, and movement reproduction accuracy. The proposed synchronization methods, including the application of the Kalman filter and the Wiener filter, demonstrated high accuracy and efficiency in creating interactive and realistic VR experiences. The study also highlights the importance of selecting optimal web technologies to enhance the performance and usability of VR applications. Optimal web technologies in this context are determined by criteria such as data processing speed, animation smoothness, ease of integration, scalability, and developer support. Performance was assessed based on the system’s response speed to user gestures and movements, which included data processing latency. Usability was analyzed based on the ease of integrating technologies into existing web applications and developer feedback on the ease of learning and using these libraries. Practical value. The research findings can be useful for developers working on creating interactive web-VR applications in various fields, including education, medicine, and e-commerce. Using React XR and React 360 allows for the rapid integration of VR technologies into the web space, enhancing the intuitiveness and naturalness of user interactions with virtual environments. The application of synchronization methods, such as the Kalman filter, ensures accurate and smooth transmission of user movements into the virtual environment, which is crucial for creating realistic and engaging VR experiences.